Detection of cadmium in soils using laser-induced breakdown spectroscopy combined with spatial confinement and resin enrichment. Issue 69 (27th November 2018) - Fu, Xinglan; Li, Guanglin; Tian, Hongwu; Dong, Daming
Abstract : The determination of heavy metals in soils is of great significance for the monitoring and control of environmental pollution. Abstract : The determination of heavy metals in soils is of great significance for the monitoring and control of environmental pollution. However, it is hard to realize fast and in situ measurements. Laser-induced breakdown spectroscopy (LIBS) is an effective method for element detection in soils, but its detection limit cannot meet the requirements of the control of soil pollution. In addition, it usually suffers splash problems and needs complex pretreatment processes before measurement. In this study, we developed a new method for the determination of cadmium in soils using LIBS. We improved the sensitivity of common LIBS, while avoiding splash problems and without complex pretreatment processes. The LIBS signal is enhanced in two ways. Firstly, the heavy metals were enriched by the cation exchange resins. And then, the LIBS signal levels were further enhanced by a sample container with spatial confinement. During this process, the soil only needs to be treated with water to achieve slurry status, rather than any complex pretreatments. We demonstrated that the detection limit for cadmium in soils is 0.132 mg kg −1 using this method.